2021
DOI: 10.5194/tc-15-2001-2021
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial supercooling and the precipitation of hydrohalite in frozen NaCl solutions as seen by X-ray absorption spectroscopy

Abstract: Abstract. Laboratory experiments are presented on the phase change at the surface of sodium chloride–water mixtures at temperatures between 259 and 241 K. Chloride is a ubiquitous component of polar coastal surface snow. The chloride embedded in snow is involved in reactions that modify the chemical composition of snow as well as ultimately impact the budget of trace gases and the oxidative capacity of the overlying atmosphere. Multiphase reactions at the snow–air interface have been of particular interest in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…We would like now to discuss the consequences of the NaCl location for the reactivity of atmospheric aerosols. Donaldson et al have detected that brine exclusion to the surface quasi-liquid layer (QLL) of ice , affects the kinetics of photolysis reactions of adsorbed polycyclic aromatic hydrocarbons (e.g., anthracene, harmine). Similarly, it is expected that such organic molecules can also be adsorbed on aerosol surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…We would like now to discuss the consequences of the NaCl location for the reactivity of atmospheric aerosols. Donaldson et al have detected that brine exclusion to the surface quasi-liquid layer (QLL) of ice , affects the kinetics of photolysis reactions of adsorbed polycyclic aromatic hydrocarbons (e.g., anthracene, harmine). Similarly, it is expected that such organic molecules can also be adsorbed on aerosol surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…The water–Cl − interaction may also include the D 2 O/H 2 O···Cl − hydrogen bond 34,37–41 except for electrostatic (or Coulomb) interaction 42,43 . The D 2 O/H 2 O–Cl − interaction should have a different strength from the SO 4 2− ···H–O–H/D–O–D hydrogen bond, as indicated from the different hydrating structures near the surface 44 and the different hydrate forms for Na 2 SO 4 and NaCl: Na 2 SO 4 ·10H 2 O (a stable compound at ambient conditions) and NaCl·2H 2 O 45 (formed only below ice point). It can be further expected that SO 4 2− has a larger hydrating scale than Cl − .…”
Section: Resultsmentioning
confidence: 99%
“…Several previous studies have analyzed the temperature-and humiditydependent phase states of NaCl particles, since they are often used as a proxy for SSA. Previous studies have found that the phase state of NaCl after efflorescence depends on the temperature at which efflorescence occurred, with anhydrous NaCl observed for efflorescence temperatures above 273 K ( Bartels-Rausch et al, 2021;Koop et al, 2000b;Peckhaus et al, 2016;Wagner et al, 2012). Since the majority of aerosol drying, including the efflorescence of the salt components of pSSA and aSSA+SMA, occurred at room temperature (Fig.…”
Section: Aerosol Generation and Characteristicsmentioning
confidence: 90%